FURTHER DEVELOPMENT OF THE ENTERPRISE INSURANCE SYSTEM AND INCREASING ITS ROLE IN THE COUNTRY'S ECONOMY - Yadgarov Akram (Scholar Express Journals, 2024)
Insurance is one of the key activities in a globalised financial and economic environment. Through its benefits, it offers income, life and property protection to the insured and their keens, as well as income accumulation that can be used at retirement to help preserve the desired lifestyle or living standards. Motivated by this end of insurance, the goal of this paper is to study the contribution of insurance growth to economic growth, by employing the benefit side of the insurance activity, next to the acquisition side that has already been considered.
Keywords: agricultural sector; agricultural insurance; income level of agricultural enterprises